Evolution and ecology of seed internal morphology in relation to germination characteristics in Amaranthaceae - Vandelook, Filip (Ann Bot, 2021)
BACKGROUND AND AIMS: Internal seed morphological traits such as embryo characteristics and nutritive tissue can vary considerably within a plant lineage. These traits play a prominent role in germination processes and the success of seedling establishment, and are therefore under high selective pressure, especially in environments hostile to seedlings, such as arid, saline or highly dynamic habitats. We investigated the relationships of seed internal morphology and germination characteristics of 84 species of Amaranthaceae s.l., a family with numerous lineages that have adapted to stressful growing conditions. METHODS: We used seed cross-sections to assess embryo type and the ratios of embryo to seed surface and radicle to cotyledon length. Furthermore, seed mass, mean time to germination, habitat preferences and further plant traits such as C(3) or C(4) photosynthesis and life form were compiled for each species. Data were analysed using phylogenetic comparative methods. KEY RESULTS: We found embryo type (λ = 1), log seed mass (λ = 0.86) and the ratio of embryo to seed size (λ = 0.78) to be evolutionarily stable, with an annular embryo as ancestral in the family. Linked to shifts to the three derived embryos types (spiral, horseshoe-shaped and curved) is an increase in the ratio of root to cotyledon length and a reduction of nutritive tissue. We observed stabilizing selection towards seeds with relatively large embryos with longer radicles and less nutritive tissue that are able to germinate faster, especially in lineages with C(4) photosynthesis and/or salt tolerance. CONCLUSIONS: We conclude that the evolutionary shift of nutrient storage from perisperm to embryo provides an ecological advantage in extreme environments, because it enables faster germination and seedling establishment. Furthermore, the evolutionary shift towards a higher ratio of root to cotyledon length especially in small-seeded Amaranthaceae growing in saline habitats can provide an ecological advantage for fast seedling establishment.